Penyuluhan Fisioterapi Mengenai Breathing Exercise Untuk Dyspnea Pada Lansia di Poslansia RW 39A Mojosongo - Tiara Paramitha Sugiri Syah Putri; Umi Budi Rahayu (Universitas 45 Surabaya, 2024)
According to WHO, an elderly person is someone who has reached the age of 60 years. At this age, elderly people experience setbacks or a decrease in function, one of which is changes and a decrease in the ability of the respiratory system, so it is not uncommon for elderly people to complain of dyspnea. One of the physiotherapy treatments for dyspnea is breathing exercises using pursed lip breathing and diaphragmatic breathing techniques. This outreach activity aims to enable the elderly to know and apply breathing exercises. The series of activities include preparation, counseling and evaluation. The evaluation was carried out by comparing the results of the pre-test and post-test that had been carried out. It was found that there was an increase in the knowledge of the elderly regarding breathing exercises for dyspnea.